Integrating Sensory Feedback into a Neural Bypass Device - Schmitz, Ceci (Kansas State University. K-State Libraries, 2022)
The objective of the project was to identify a problem or opportunity with a company process or product and propose a change based on thorough research. For my project, I chose the NeuroLife neural bypass device produced by Battelle. The device was designed to provide hundreds of thousands of people with the opportunity to overcome devastating neurological damage and disorders. However, the current design focuses only on restoring motor function. As a result, the patient faces challenges and limitations when moving a limb due to lack of immediate feedback to the brain to inform subsequent movements. My proposed change was to integrate sensory information to build a bidirectional neural bypass device to improve patient usability and device performance. Therefore, I investigated three primary cortical stimulation techniques being researched and developed for restoring sensory feedback. I also evaluated each technique based on prominent challenges that accompany brain-computer interfaces (BCIs). The three main methods for stimulating the central nervous system include magnetic stimulation, optogenetics, and electrical stimulation. The areas I used to evaluate each method were tissue damage, specificity of neuronal excitement, ethical considerations, and types of sensory information that have been successfully restored. Based on my research and the evaluation criteria, I propose integrating electrical stimulation into a neural bypass device because it would be the most feasible and reliable. I also provide recommendations for Battelle as possible steps for implementing my proposal.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Keywords: Neurolife; Battelle; Optionetics; Neural Bypass Device; Brain-Computer Interfaces; Neurological Damage